Engagement in the Cyber Socialization of Youth and its Socio-demographic Characteristics as Predictors of Unembodiment on the Internet - N.V. Kochetkov; D.P. Kudriashov (Социальная психология и общество)
Objective. To consider involvement in cyber socialization as a predictor of unembodiment in the Internet among youth. Background. Unembodiment is a phenomenon that appears as a result of using the Internet and negatively affects the development of personality. On the other hand, using the Internet can provide a resource for socialization in the real world. Study design. After the psychodiagnostic stage of the study, the theoretically distinguished components of unembodiment on the Internet and engagement in cybersocialization were compared according to controlled parameters – gender, level of education, form of employment, marital status, and a regression model of unembodiment was built. Participants. The sample consisted of 106 respondents (26,4% men, 73,6% women), aged from 18 to 25 years (M = 22,14; SD = 1,6). Measurements. The cyber socialization engagement questionnaire, questionnaire “Unembodiment in the Internet”. Results. Most of the respondents have average levels of unembodiment, as well as engagement in cybersocialization. Unembodiment on the Internet and engagement in destructive cybersocialization are higher among males, unmarried respondents, unemployed, as well as among respondents with incomplete higher education. Predictors of unembodiment on the Internet are gender, the form of employment and the severity of destructive engagement in cybersocialization. Conclusions. Unembodiment on the Internet manifests itself with destructive engagement in cybersocialization. Constructive engagement in cybersocialization is observed among respondents who can be called socialized in real life – those who have a job and a family. Network activity aimed at socialization in the real world can lead to a harmonious coexistence of reality and virtuality in a person and socialization in both these spheres.